Targeting Inflammation in CKD-Related Anemia: The Emerging Role of Lactoferrin as an Adjunctive Therapy - Harsh J Shah; Jacky K Pariyani; Kalyani V Shinde; Dharmil P Pandya; Bhakti A Dave; Megha M Lokhande (Turkish Journal of Internal Medicine, 2026)
Objective: Chronic kidney disease (CKD)-associated anemia is substantially driven by chronic inflammation, which promotes hepcidin upregulation, restricts iron availability, and impairs erythropoiesis. Conventional therapies, including erythropoiesis-stimulating agents and iron supplementation, primarily address erythropoietin deficiency and iron depletion but do not directly target the underlying inflammatory pathways. This narrative review evaluates the role of inflammation in CKD-associated anemia and examines the emerging potential of lactoferrin as an adjunctive therapeutic approach.Methods: This narrative review was based on a literature search of PubMed, Scopus, and Google Scholar for articles published between January 2000 and March 2026, using combinations of the terms “chronic kidney disease,” “anemia,” “inflammation,” “hepcidin,” and “lactoferrin.”Results: Chronic inflammation contributes to CKD-associated anemia through interleukin-6-mediated hepcidin upregulation, ferroportin degradation, impaired iron absorption and mobilization, and cytokinemediated suppression of erythropoiesis. Lactoferrin, an iron-binding glycoprotein with anti-inflammatory, immunomodulatory, and iron-regulatory properties, may counter these mechanisms by reducing inflammatory signaling, modulating hepcidin expression, and improving functional iron availability. Clinical studies have generally reported improvements in hemoglobin, with several studies also reporting favorable changes in hepcidin levels and inflammatory markers, supporting the potential anti-inflammatory and iron-regulatory effects of lactoferrin.Conclusion: Lactoferrin represents a promising adjunctive approach for inflammation-driven CKD-associated anemia, particularly functional iron deficiency. Its potential effects on the IL-6–hepcidin–ferroportin axis may complement established ESA and iron therapy.